Study on respiratory problems and respiratory function amongst females exposed to biomass fuel and gas/ electricity fuel in a district of Bangladesh (Community Based Medical Journal, 2014)
Indoor air pollution from biomass smoke is now regarded as public health hazard in the developing world causing different respiratory diseases. A cross-sectional study was conducted to see the prevalence of respiratory disease and status of respiratory function among female biomass fuel users and gas/electricity fuel users in a selective area of Bangladesh. A total of 103 females from Madla, a rural area under Bogra District of Bangladesh, which having good communication facilities, meeting the defined enrollment criteria for biomass fuel group were selected purposively as cases, while 101 females from the urban households from Thanthania in the same district, meeting the defined eligibility criteria for controls were included in gas/electricity fuel group. The participants were interviewed on a semi-structured questionnaire from March to June 2007. Moreover, peak expiratory flow rate (PEFR) of 98 participants from each group was measured as a lung function parameter. In the biomass group, majority (61.6%) used open type of kitchen, 21.2% partially closed kitchen, 11.1% closed and 6.1% closed non-ventilated kitchen. Nearly three-quarter (73%) of the gas/electricity group used closed ventilated type of kitchen, 26% used partially closed kitchen and only 1 case used open kitchen. Nearly one-quarter (24%) of the biomass group had habit of taking beetle-nut compared to only 3% of the gas/electricity group and chewing tobacco was also revealed to be proportionately higher in the former group (22.8%) than that in the latter group (4%) (p